Creating ionic pathways in solid-state polymer electrolyte by using PVA-coated carbon nanofibers. (3rd May 2021) - Huang, Feng; Singer, Gerald; Zhou, Yang; Sha, Zhao; Chen, Junyan; Han, Zhaojun; Brown, Sonya A.; Zhang, Jin; Wang, Chun H.
Abstract: Solid-state polymer electrolytes (SSPE) have emerged as a safer and more durable alternative to liquid electrolytes in future batteries and supercapacitors. Herein, we present a novel approach to enhance the ionic conductivity of a solid epoxy-ionic liquid (IL) nanocomposite electrolyte by creating ionic pathways in the polymer phase and linking the liquid phase using carbon nanofibers (CNFs) coated with Poly(vinyl alcohol) (PVA). The CNFs are covalently functionalized with PVA and are then dispersed in an epoxy/IL (1:1) mixture using ultrasonication and a three-roll mill. The electrical and mechanical properties of the resultant solid electrolyte are characterized by impedance spectroscopy and tensile tests. The results show that PVA-modified CNFs increase the ionic conductivity of the SSPE (which is a nanocomposite of epoxy and IL) by a factor of 38, from 8.32 × 10 −4  S/m to 3.18 × 10 −2  S/m, while Young's modulus is slightly reduced by 10% to retain a modulus around 800–850 MPa. The huge improvement in the ionic conductivity of the solid electrolyte is due to the greatly improved ion conduction along with the interface between the epoxy and the interconnected CNFs in the epoxy phase. To assess whether the ionic conductivity can be further increased by aligning CNFs, an external electric field is applied during the curing of the epoxy. Results show that there is no discernible improvement in the electrical and mechanical properties of the solid electrolyte. The new CNF-reinforced SSPE offers great potential for high-performance structural batteries or supercapacitors. Graphical abstract: Image 1 Highlights: Carbon nanofibers (CNFs) create ionic pathways in the epoxy phase, increasing the ionic conductivity by 29 times. PVA-modification of CNFs further improves the ionic conductivity by an additional 33 % from 2.3810 -2 S/m to 3.1810 -2 S/m. External electric field has been found to yield little noticeable improvement in mechanical and electrical properties.